ESUPPLIER APPROVAL PROCESS ON COMPOSITES’ PRODUCT-BASED MANUFACTURERS - Mahmood, W.H.W.; Saedin, M.R.; Muhamad, M.R.; Rahman, M.S.A. (Journal of Advanced Manufacturing Technology (JAMT), 2015)
The supplier is one of the keys to success in an organization and can also be the cause of the collapse of the company in which the supplier is able to introduce a number of problems such as supply of poor raw materials, shipping delays, poor services and failure to comply the requirement. Hence, approved supplier list has been used as a reference and a guide to the purchasing department to sourcing a trusted supplier. Therefore the development of process flow for approved supplier list must be done right for the effectiveness of this system. This paper analyzed supplier approval process on four selected companies specializing in composite product and manufacturing. The data collection consists of a series of semi-structured interview with supply chain personnel, documentation review and observation. These findings indicated that the same concept such as system audit, questionnaire and supplier assessment was used in a process of selecting potential suppliers prior to being inserted in the approved supplier list. Besides, the study identified that different companies (same business nature, but different product) had their distinctive ways in developing the process flow of the approved supplier list. The results can be used as reference to other companies to restructure their process flow for approved supplier list; focusing on their business goal and objective.